Epistemic Injustice - Simpson, Hannah (11807030) (2019)
“Epistemic injustice” is a fairly new concept in philosophy, which, loosely speaking, describes a kind of injustice that occurs at the intersection of structures of the social world and knowledge. While the concept was first put forward in the 1990’s, the most significant publication on the topic is Miranda Fricker’s book Epistemic Injustice: Power and the Ethics of Knowing, which was published in 2007. Since then, there has been something of an explosion of literature on the topic of epistemic injustice. However, the concept of epistemic injustice is one that is poorly understood. While Epistemic Injustice offers extensive analysis of some aspects of epistemic injustice, it does a poor job of explaining, overall, what epistemic injustice actually is, limiting most of that explanation to a small section in the introduction of the book. The way that epistemic injustice is presented in this section is highly ambiguous, with key terms being loosely defined (if at all), and the necessary and sufficient conditions of something being an epistemic injustice are left unclear. This remains unresolved in the literature beyond Fricker’s account: while there has been some progression in how we think about epistemic injustice beyond what Fricker’s work provides us with, there has been a general failure to adequately recognize and address the ambiguities of the Frickerian account of epistemic injustice. In this thesis, I aim to show that, despite superficial impressions to the contrary, the Frickerian account is fundamentally ambiguous and incomplete. Moreover, later attempts to address these issues by subsequent theorists have failed. This project, however, is not in vain. I conclude by proposing a new account of epistemic injustice that overcomes these problems with the Frickerian account, offering a way of understanding epistemic injustice that is both philosophically satisfying and practically useful.